Evidence That Frame of Reference Effects Can Reduce Socially Prescribed Perfectionism - Bouguettaya, Ayoub; Cruwys, Tegan; Moulding, Richard; King, Ross; Bliuc, Ana-Maria (Frontiers in Psychology, 2019)
Socially prescribed perfectionism appears to drive disordered eating behaviour in young women, usually via messages from fellow women. Social psychological research suggests that framing effects can be manipulated to reduce the effect of unhealthy messages. This research used contrasting messages about perfectionism to reduce perfectionism among female dieters. We recruited 147 female dieters (Mage=25.11) for a between-subjects experimental study. While completing an online questionnaire, participants were exposed to one of three sets of blog posts, which varied in content and source. These three conditions always had one anti-perfectionism message from a woman. This was presented along with either a high perfection message from a man, a high perfectionism message from a woman, or both of these messages. After reading the blog posts, women were asked to fill out a scale assessing their levels of socially prescribed perfectionism. When participants were exposed to an anti-perfectionism message from a woman, paired with a high-perfectionism message from a man, participants showed lower socially-prescribed perfectionism than when both high and anti-perfectionism messages came from two women. These findings imply that strategies designed to reduce socially-prescribed perfectionism may benefit from including contrasting messages, as this may shift perceived perfectionism norms. Implications for social interventions are discussed.